Comprehensive off‐line CCC × LC‐DAD‐MS separation of Cyclopia pubescens Eckl. & Zeyh. phenolic compounds and structural elucidation of isolated compounds. Issue 3 (17th August 2020) - Walters, Nico A.; de Beer, Dalene; de Villiers, André; Danton, Ombeline; Hamburger, Matthias; Joubert, Elizabeth
Abstract: Introduction: The minor phenolic constituents of Cyclopia pubescens Eckl. & Zeyh. are unknown and one dimensional (1D) liquid chromatography (LC) is unable to provide sufficient separation. Methodology: A two‐dimensional (2D) LC method incorporating normal‐phasehigh performance countercurrent chromatography (NP‐HPCCC) in the first dimension ( 1 D) and reversed‐phase ultra‐high‐performance liquid chromatography (RP‐UHPLC) as the second dimension ( 2 D) was developed. The analytical HPCCC method was subsequently scaled up to semi‐preparative mode and fractions pooled based on phenolic sub‐groups. The phenolic compounds in selected fractions were subsequently isolated using RP‐HPLC on a C18 column. Isolated compounds were identified by nuclear magnetic resonance (NMR) spectroscopy. The absolute configurations of compounds were determined by optical rotation and electronic circular dichroism spectra. Sugars were identified by gas chromatography‐mass spectrometry (GC–MS) analysis. Results: The comprehensive off‐line 2D CCC × LC method gave a good spread of the phenolic compounds. Orthogonality calculated using both the convex hull and conditional entropy methods were 81%. High‐resolution mass spectrometric fragmentation spectra obtained from a quadrupole‐time‐of‐flight instrument and ultraviolet‐visible (UV‐vis) spectral data were used to (tentatively) identify 32 phenolic compounds from the analytical CCC fractions. Of the seven isolated compounds, (2 S )‐5‐ O ‐[α‐l ‐rhamnopyranosyl‐(1 → 2)‐β‐d ‐glucopyranosyl]eriodictyol (3 ) and (2 S )‐5‐ O ‐[α‐l ‐rhamnopyranosyl‐(1 → 2)‐β‐d ‐glucopyranosyl]‐5, 7, 3′, 4′‐tetrahydroxyflavan (4 ) were newly identified in all plants. The other isolated compounds were identified as (2 S )‐5‐ O ‐[α‐l ‐rhamnopyranosyl‐(1 → 2)‐β‐d ‐glucopyranosyl]naringenin (1 ), R ‐neo‐eriocitrin (2 ), 3‐ O ‐α‐l ‐arabinopyranosyl‐3, 4‐dihydroxybenzoic acid (5 ), 4‐ O ‐β‐d ‐glucopyranosyl‐ Z ‐4‐hydroxycinnamic acid (6 ) and 4‐(4′‐ O ‐β‐d ‐glucopyranosyl‐4′‐hydroxy‐3′‐methoxyphenyl)‐2‐butanone (7 ). Conclusions: Among the 32 compounds (tentatively) identified, only six were previously identified in Cyclopia pubescens using 1D LC. Most of the isolated compounds were also identified for the first time in Cyclopia spp., improving the knowledge of the minor phenolic compounds of this genus. Abstract : Limited separation by one‐dimensional (1D) liquid chromatography (LC) and lack of knowledge about minor phenolic constituents of Cyclopia pubescens provided incentive to develop a comprehensive offline two‐dimensional (2D) normal‐phase‐high performance countercurrent chromatography (NP‐HPCCC) × reversed‐phase‐ultra‐high‐performance liquid chromatography (RP‐UHPLC) method with high orthogonality (81%). This enabled tentative identification of 32 phenolic compounds. The analytical HPCCC method was up‐scaled, fractions pooled based on phenolic sub‐groups and seven compounds were isolated and their structures elucidated. Of these, (2 S )‐5‐ O ‐[α‐l ‐rhamnopyranosyl‐(1 → 2)‐β‐d ‐glucopyranosyl]eriodictyol (3 ) and (2 S )‐5‐ O ‐[α‐l ‐rhamnopyranosyl‐(1 → 2)‐β‐d ‐glucopyranosyl]‐5, 7, 3′, 4′‐tetrahydroxyflavan (4 ), were newly identified in all plants.